PENGARUH PEMASARAN DIGITAL, PERSEPSI KUALITAS, DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN SEPATU LOKAL DI MARKETPLACE - Tedy Setiawan; Rahmat Hidayat (Pusat P2M Politeknik Negeri Batam, 2022)
This main object of this research is to know relation of digital marketing, perception of quality, and brand image to purchase decision of local shoe in marketplace. This research using survey with questionnaire to 111 respondents that ever buy local shoe in marketplace Shopee or tokopedia. Method that use to test the hypothesis is multi linear regression, t test, F test and coefficient of determination test. The result is there is positive and significant impact fr digital marketing, quality perception, brand image to purchase decision of local shoes in marketplace partially and simultaneous. The results show the adjusted R Square value of 0.496, this means that the digital marketing variables, perceived quality, and brand image 49.6% affect the decision to buy local shoes in the marketplace and the remaining 50.4% comes from other independent variables.